Hosoya and Harary Polynomials of Hourglass and Rhombic Benzenoid Systems. (9th April 2020) - Cheng, Zhong-Lin; Ali, Ashaq; Ahmad, Haseeb; Naseem, Asim; Chaudhary, Maqbool Ahmad
Abstract : In the fields of chemical graph theory, topological index is a type of a molecular descriptor that is calculated based on the graph of a chemical compound. In 1947, Harry Wiener introduced "path number" which is now known as Wiener index and is the oldest topological index related to molecular branching. Hosoya polynomial plays a vital role in determining Wiener index. In this report, we compute the Hosoya polynomials for hourglass and rhombic benzenoid systems and recover Wiener and hyper-Wiener indices from them.